Peran Praktik Akuntansi Keuangan Dan Pemahaman Perpajakan Terhadap Kepatuhan Pajak Umkm Dengan Kemampuan Teknologi Digital Sebagai Variabel Moderasi - Perdanakusuma, Fathul Hilal; Seventeen, Winny Lian (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
This study aims to analyze the influence of financial accounting practices and tax understanding on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs), with digital technology capability as a moderating variable. MSMEs play a strategic role in the national economy; however, their tax compliance level remains relatively low due to a lack of tax understanding, inadequate bookkeeping, and limited utilization of technology. This research employs a quantitative approach with a causal associative research design. The results show that financial accounting practices and tax understanding have a positive and significant effect on MSME tax compliance, with the greatest influence stemming from accounting practices. However, digital technology capability is not proven to moderate the relationship between accounting practices or tax understanding and tax compliance. These findings indicate that the use of digital technology in MSMEs' tax-related activities remains low and suboptimal. This study recommends the importance of training and assistance in accounting, taxation, and the use of digital technology for MSME actors, and contributes to the development of accounting and taxation literature in the small business sector in the digital era.